Fluid Chemistry of Mid-Ocean Ridge Hydrothermal Vents: A Comparison between Numerical Modeling and Vent Geochemical Data. (31st October 2018) - Pierre, Samuel; Gysi, Alexander P.; Monecke, Thomas
Abstract : Seawater-basalt interaction taking place at mid-ocean ridges was studied using numerical modeling to determine the compositional evolution of hydrothermal fluids and associated alteration mineralogy forming within newly emplaced crustal material. Geochemical modeling was carried out in a closed seawater-basalt system at discrete temperature intervals between 2 and 400°C at 500 bars, varying fluid/rock ratios, and secondary mineral assemblages representative of basalt alteration in natural systems. In addition to temperature, the fluid/rock ratio has a fundamental control on the resulting system chemistry. At rock-buffered conditions (low fluid/rock ratios), the mineral-solution equilibrium was characterized by high cation to proton activity ratios for a Ca 2+ /( a H + ) 2 and a Na + / a H + and very low dissolved Mg concentrations due to the precipitation of smectites and chlorite. A complex secondary mineral alteration assemblage dominated by Ca- and Na-bearing minerals including zeolites, calcite, epidote, prehnite, clinozoisite, and albite was predicted to form. The resulting fluid composition was alkaline and reduced relative to ambient seawater, with Eh values ranging between −0.2 and −0.6 V. In contrast, seawater-buffered conditions (high fluid/rock ratios) resulted in lower cation to proton activity ratios for a Ca 2+ /( a H + ) 2 and a Na + / a H + and higher dissolved Mg concentrations comparable to the value of this element in ambient seawater. A more simple mineral assemblage was predicted to form at these conditions with the predominance of Al-Si- and Mg-bearing minerals including kaolinite, quartz, and talc in addition to large amounts of anhydrite. The resulting fluid composition was mildly acidic and oxidized relative to seawater with Eh values ranging between −0.2 and 0 V. These modeling results were compared to a compilation of submarine hydrothermal vent fluid compositions from mid-ocean ridge settings and analogous basalt-dominated environments. The agreement obtained between the simulations and the compiled fluid data indicates that mid-ocean ridge hydrothermal processes can be closely reproduced by mineral-solution equilibria for a broad range of temperatures and fluid/rock ratios.